A study of locally designed automated library systems in selected academic libraries in Metro Manila - Magtulis, Philip E.; Sison, Josephine C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2000)
Three automated library systems namely, Libro 2000 of PISCES Publishing being used by the Philippine Normal University, dBEIS of Don Bosco Technical College in Mandaluyong and FEU-FERN Microsoft Access based library system were studied. The creators and designers of the said library systems, the head librarians and the librarians were interviewed and surveyed regarding their overall perception on the three automated library systems. The three automated library systems were compared against foreign designated automated library systems, and the locally designed library systems were shown to have almost the same capabilities and functions as those of the foreign designed systems. The locally designed systems were also found to cost less and are adapted to local library settings which give them an edge over foreign designed systems.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: ALS (Computer System).; Don Bosco Technical College Library; Far Eastern University Library; Philippine Normal University Library